A Practical guide to localization - Esselink, Bert. (Amsterdam ; Philadelphia : John Benjamins Pub. Co., 2000)
A Practical Guide to Localization was written for technical translators, localization engineers, testing engineers, desktop publishers, project managers, and anyone else who may be involved in the release of multilingual products. In this second edition, translators can learn more about localizing software, online help and documentation files, and the latest translation technology tools. Localization engineers can learn all about developing, engineering, and testing multilingual software and online help projects. For project managers, there is all the information needed for planning translation.
A Practical Guide to Localization; LANGUAGE INTERNATIONAL WORLD DIRECTORY; Editorial page; LCC data; Preface; Table of contents; Introduction; Internationalization; Software Translation; Software Engineering; Software Quality Assurance; Online Help Translation; Online Help Engineering and Testing; Documentation Translation; Desktop Publishing; Graphics Localization; Translation Technology; Terminology; Project Evaluations; Project Management; Appendix A: Glossary of Terms; Appendix B: Localization in the New Millennium; Index.
Revised edition of: A practical guide to software localization.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Software localization; Software documentation; Logiciels -- Documentation; Logiciels -- Internationalisation; COMPUTERS -- Programming -- Open Source; COMPUTERS -- Software Development & Engineering -- Tools; COMPUTERS -- Software Development & Engineering -- General; Software documentation; Software localization; Datenverarbeitung; Fachsprache; Computerlinguistik; Übersetzung